Milli Mücadele Döneminde Savaş Edebiyatımız - Gülşen, Hacer (My University, 2008)
Türk milleti bir ölüm kalım savaşı vermiş, ordu -millet el ele mi lll bir mücadele içine girmiştir. Ölüm kalım mücadelesi verirken bir yandan da yazarlarımız savaşın sıcaklığını hissettiren yazılar yazmışlar, bu şekilde cephe gerisinden savaşan askerlerimize cesaret ve kuvvet vermişlerdir. Her milletin bir savaş edebiyatı ve bu edebiyat ürünlerini topladığı bir kütüphanesi olduğunu belirten yazarlarımız, bizim de savaş edebiyatı eserlerimiz ve bir kütüphanemiz olması gerektiğini ısrarla savunmuşlardır.

Turkish National was giving the struggle of living and death, the army an the people was going into a national stnıggle hand in hand. While The Turkish people had been struggling for lıving and death, our writers had been writen about the heat of the war and had been given courage and strength to our sol di ers from the back of the fronts by this way. The Turkish writers who noticed that all the nations has a war literature and has a library that includes the products of this literal kin ds, insist on setting up a this kind of library
Our War Literature in The National Struggle
Keywords: Türk Edebiyatı; Milli Mücadele; Savaş; Cephe; Savaş Edebiyatı; Kütüphane; Turkish Literature; National Struggle; War; Front; War Literature; Library